2017
DOI: 10.1101/gad.294348.116
|View full text |Cite
|
Sign up to set email alerts
|

Single tumor-initiating cells evade immune clearance by recruiting type II macrophages

Abstract: Tumor infiltrated type II (M2) macrophages promote tumorigenesis by suppressing immune clearance, promoting proliferation, and stimulating angiogenesis. Interestingly, macrophages were also found to enrich in small foci of altered hepatocytes containing liver tumor-initiating cells (TICs). However, whether and how TICs specifically recruit macrophages and the function of these macrophages in tumor initiation remain unknown due to technical difficulties. In this study, by generating genetically defined liver TI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
186
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(201 citation statements)
references
References 49 publications
13
186
2
Order By: Relevance
“…Relevant to these findings is a recent report by Guo et al (88) who utilized a different murine HCC model induced by the hydrodynamic tail injection of mutant YAP. Although these animals do not develop tumors until 12-16 weeks, the homing of macrophages to YAP+ tumor-initiating hepatocytes could be detected as early as two days postinjection and well before the development of any discernible tumors.…”
Section: Discussionmentioning
confidence: 78%
“…Relevant to these findings is a recent report by Guo et al (88) who utilized a different murine HCC model induced by the hydrodynamic tail injection of mutant YAP. Although these animals do not develop tumors until 12-16 weeks, the homing of macrophages to YAP+ tumor-initiating hepatocytes could be detected as early as two days postinjection and well before the development of any discernible tumors.…”
Section: Discussionmentioning
confidence: 78%
“…When Hippo signaling is inactivated, YAP/TAZ enter the nucleus, bind to the transcription factor TEADs, and induce gene transcription. Recently, the effects of the Hippo pathway components on tumor initiation and growth in the context of reciprocal interactions between tumor cells and host anti-tumor immune responses have emerged Guo et al, 2017;Kim et al, 2017;Zhang et al, 2017b). Previous studies have convincingly demonstrated the Hippo pathway as a suppressor signal for cellular transformation and tumorigenesis (Moroishi et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…However, the remarkable conclusion that can be drawn from the study by Guo et al (2017) is that even single tumor cells at the very beginning of tumorigenesis become able to evade immune clearance by recruiting macrophages, and this is due to the ability of specific activated oncogenes to directly attract these cells. Aside from its remarkable biological interest, this study is not devoid of potential medical implications, as it suggests that the interference with the activation of the Hippo pathway, in addition to its possible direct effects on parenchymal tumor cells, may unleash an efficient antitumor response.…”
mentioning
confidence: 99%
“…It is therefore not surprising that this pathway is frequently deregulated in tumorigenesis. The study by Guo et al (2017) investigated the possibility that the Hippo pathway may be directly involved in the recruitment of macrophages to promote liver carcinogenesis and used experimental strategies to track the interplay between macrophages and tumor-initiating cells from the very beginning of the process.…”
mentioning
confidence: 99%
See 1 more Smart Citation